Pengaruh Digital Marketing Dan Sertifikasi Halal Produk Terhadap Keputusan Pembelian Masyarakat Pada Usaha Ilhamumtaza Jambi - Ade Dea Novita; Agustina Mutia; Awal Habibah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The high promotional costs of marketing products on social media are a problem for business actors. That way, business actors can market their products directly to the field. This is the background to research entitled The Influence of Digital Marketing and Halal Product Certification on People's Purchasing Decisions for the Ilhamumtaza Jambi Business. The aim of this research is to find out the partial or simultaneous influence of digital marketing and halal product certification on people's purchasing decisions for the Ilhamumtaza Jambi business. The method used in this research is a descriptive quantitative method with 344 respondents. The technique used in sampling is purposive sampling, namely the sampling method used, and it is used to take into account a number of factors. Data collection is done distributing of questionnaires, interviews, and also documentation. The results of this research show that: (1) There is a partial significant influence of digital marketing variables and halal product certification on people's purchasing decisions for the Ilhamumtaza Jambi business. (2) The independent variables, namely the digital marketing and halal certification variables, have a positive effect (moving in the same direction) on people's purchasing decisions for the Ilhamumtaza Jambi business, with an Adjust R2 coefficient value of 0.533%. This illustrates that the contribution value of digital marketing variables and halal product certification to people's purchasing decisions is 53% and 47% influenced by other factors that are not part of this research, and the results of the effective contribution value (contribution) that are more influenced are the certification variables. halal products by 48%. In this study, researchers can take see that digital marketing can introduce products more widely, both on social media and in the field. And the existence of halal product certification becomes the most important value in determining the decision to purchase a product. Because consumers will look again at the halal logo on the product packaging. And by introducing digital marketing to this business, it can also increase buyer interest on social media from this business.